Mobile workers, contingent labour: Migration, the gig economy and the multiplication of labour - Altenried, Moritz (Environment and planning. A, 2024)
The article takes the surprising exit of the food delivery platform Deliveroo from Berlin as a starting point to analyse the relationship between migration and the gig economy. In Berlin and many cities across the globe, migrant workers are indispensable to the operations of digital platforms such as Uber, Helpling, or Deliveroo. The article uses in-depth ethnographic and qualitative research to show how the latter's exit from Berlin provides an almost exemplary picture of why urban gig economy platforms are strongholds of migrant labour, while at the same time, demonstrating the very contingency of this form of work. The article analyses the specific reasons why digital platforms are particularly open to migrants and argues that the very combination of new forms of algorithmic management and hyper-flexible forms of employment that is characteristic of gig economy platforms is also the reason why these platforms are geared perfectly toward the exploitation of migrant labour. This allows the analysis of digital platforms in the context of stratified labour markets and situates them within a long history of contingent labour that is closely intertwined with the mobility of labour.